2022
DOI: 10.3390/polym14204252
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Effective and Durable Film for Marine Fouling Prevention from PDMS/SiO2 and PDMS/PU with SiO2 Composites

Abstract: Polymer film coating with a highly hydrophobic surface property is a practical approach to prevent fouling of any structures in the marine environment without affecting marine microorganisms. The preparation of a polymer coating, from a simple and easy method of solution blending of hydrophobic polydimethylsiloxane elastomer and hydrophilic polyurethane with SiO2, was carried out in this study, with the aim of improving characteristics, and the coating demonstrated economic feasibility for antifouling applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…combined rough electrodeposited 14SiO 2 (E‐SiO 2 ) films, possessing low energy, and durable PDMS aiming to mechanical durability of superhydrophobic surfaces. [ 43 ] The resulting substrate showed morphologies unchanged after being subjected to 40 cycles of abrasion, which was then concluded that PDMS modifier with low surface energy played a significant role in improvement of mechanical stability. For steel coatings, a composite consisting of 10‐15 μm PDMS films and hydrophobic silica nanoparticle demonstrated an excellent barrier property and offered protection for nearly 80 days.…”
Section: Polymers Coatingmentioning
confidence: 96%
“…combined rough electrodeposited 14SiO 2 (E‐SiO 2 ) films, possessing low energy, and durable PDMS aiming to mechanical durability of superhydrophobic surfaces. [ 43 ] The resulting substrate showed morphologies unchanged after being subjected to 40 cycles of abrasion, which was then concluded that PDMS modifier with low surface energy played a significant role in improvement of mechanical stability. For steel coatings, a composite consisting of 10‐15 μm PDMS films and hydrophobic silica nanoparticle demonstrated an excellent barrier property and offered protection for nearly 80 days.…”
Section: Polymers Coatingmentioning
confidence: 96%
“…As the silicone powder content increased, the contact angle of the compounds increased from 73 (pure PLA) to 91 (3 wt% silicone powder addition), which can be attributed to the synergistic effect of the low surface energy of PDMS and the micro/ nanostructure of SiO 2 . 58 When the content of silicone powder exceeded 3 wt%, the contact angle of the compound decreased slightly. When combined with the SEM findings, it reveals that the agglomeration of SiO 2 limits the improvement in the hydrophobic performance Figure 9.…”
Section: Contact Angle Test Of Hydrophobic Pla Compounds and Fibersmentioning
confidence: 99%
“…When PDMS segments migrated to the surface, the -CH 3 in PDMS tended to combine with the polarity of polyurethane internally, while the Si-O chains tended to bugle in the air, forming a hydrophobic surface. [30][31][32] Therefore, when the contents of PDMS reached 10 wt%, as silicon element was enriched to saturated state on polyurethane surface, increasing PDMS contents would not reduce surface energy of Si-MPTUs.…”
Section: Static Contact Anglementioning
confidence: 99%